Innovative Methods to Enhance Seed Potato Production - Sadawarti, Murlidhar J.; Buckseth, Tanuja; Singh, S. P.; Kumar, Vinod; Singh, Rajesh K.; Sharma, Ashwani K.; Katare, Subhash; Jatav, Pooja; Deora, Deepanshi; Khambalkar, Priyadarshani; et al. (Chronicle of Bioresource Management, 2025)
Ensuring the availability of high-quality potato seed at a reasonable price and at the appropriate time continues to be a significant issue for government seed-producing agencies globally. Traditional methods of seed potato production encounters numerous challenges such as a low multiplication rate (1:6), the buildup of degenerative diseases, perishability, bulkiness, and a sluggish process for generating 100% healthy seed stock. To tackle these issues, rapid multiplication techniques (RMTs) have become increasingly important. Among these, the aeroponic system has impressive multiplication rate (1:20–80) and apical rooted cuttings (ARC) and sprout cuttings has potential for large-scale seed multiplication, being both economical and beneficial for farmers. Each ARC cutting can yield 7–15 tubers, while a well-developed sprout cutting can produce 6–11 tubers per sprout and ongoing research is concentrating on optimizing them in terms of agronomic practices, fertilizer combinations, plant health management, cost–benefit ratios, and storage. These methods are also being actively encouraged for incorporation into formal seed potato production systems, with the goal of enhancing seed availability and accessibility for farmers.